Influence of cell wall peptidoglycan of Lactobacillus delbrueckii on specific immunoprophylaxis of porcine epidemic diarrhea. - Масюк, Микола Миколайович; Masiuk, Mykola; Кокарєв, Андрій Вікторович; Kokariev, Andriy; Глебенюк, Володимир Володимирович; Hlebeniuk, Volodimir; Василенко, Тетяна Олександрівна; Vasylenko, Tetyana (Издательский дом Биофлюкс, 2020)
Investigate the effect of peptidoglycan of L. delbrueckii cell wall on the specific immunoprophylaxis of PED. An experimental and control group of sows with 10 heads each. The sows of the experimental group at 60, 75 and 90 days of gestating were administered GMPP at a dose of 0.05 mg GMPP per 1 kg of weight. The sows of the control and experimental groups were immunized with autogenous inactivated vaccine against PEDV at 90 and 100 days of gestation. To determine specific IgG in sows and piglets born from them, blood samples were taken at 1, 5 and 10 days after farrowing and days of life respectively. The application of the GMPP preparation to sows under immunization against PED contribute to increases the seroconversion of IgG by 42% and their homogeneity by 17%, as well as contributes to the development of specific colostral immunity higher by 33% which is stored in more than 70% of the animals during the first 10 days of life in comparison to the control group. Application of the GMPP preparation contributes to increase the level of antigen specific IgG in the blood of sows and provides the development of higher levels of colostral immunity in piglets.Дослідити вплив пептидоглікану клітинної стінки L. delbrueckii на специфічну імунопрофілактику ПЕД. Експериментальний і контрольна група свиноматок по 10 голів у кожній. Свиноматкам експериментальної групи на 60, 75 та 90 день вагітності вводили GMPP в доза 0,05 мг GMPP на 1 кг ваги. Свиноматок контрольної та експериментальної груп імунізували аутогенною інактивованою вакциною проти PEDV на 90 та 100 дні гестації. Для визначення специфічного IgG у свиноматок та поросят, що народилися від них, брали проби крові на 1, 5 та 10 дні після опоросу та дні життя відповідно. Застосування препарату GMPP для свиноматок, які перебувають під імунізацією проти PED сприяють збільшенню сероконверсії IgG на 42% та їх однорідності на 17%, а також сприяє розвитку специфічний колостральний імунітет вище на 33%, який зберігається у понад 70% тварин протягом перших 10 днів життя порівняно з контрольна група. Застосування препарату GMPP сприяє підвищенню рівня антиген-специфічного IgG у крові свиноматок та забезпечує розвиток вищих рівнів колострального імунітету у поросят.
Вплив пептидоглікану клітинної стінки Lactobacillus delbrueckii на специфічну імунопрофілактику епідемічної діареї свиней
Keywords: PEDV; PEDV; колостральний імунітет; colostral immunity; IgG; IgG; пептидоглікан; peptidoglycan; поросята; piglets